2021
DOI: 10.1177/15330338211004944
|View full text |Cite
|
Sign up to set email alerts
|

LAMB1 Is Related to the T Stage and Indicates Poor Prognosis in Gastric Cancer

Abstract: Background and Objective: Gastric cancer (GC) is a common tumor malignancy with high incidence and poor prognosis. Laminin is an indispensable component of basement membrane and extracellular matrix, which is responsible for bridging the internal and external environment of cells and transmitting signals. This study mainly explored the association of the LAMB1 expression with clinicopathological characteristics and prognosis in gastric cancer. Methods: The expression data and clinical information of gastric ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Since a large number of M2-type macrophages infiltrate HCC caused by HBV and HCV, and the activation of PI3K-Akt-mTOR pathway is related to the M2 polarization of macrophages (11,24), Through literature review, it was found that 13 differential genes (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), including mTOR, PIK3CA, AKT2, and PIK3CB, involved in the M2-type polarization of macrophages, according to the genes related to M2-type polarization. We first analyzed the expression of these 13 genes in HBV-HCC and HCV-HCC, and found that mTOR was down-regulated while other genes were up-regulated (Figure S3), which was consistent with the molecular characteristics of macrophage polarization.…”
Section: Correlation Analysis Between Hub Genes and Immune Pathwaymentioning
confidence: 99%
“…Since a large number of M2-type macrophages infiltrate HCC caused by HBV and HCV, and the activation of PI3K-Akt-mTOR pathway is related to the M2 polarization of macrophages (11,24), Through literature review, it was found that 13 differential genes (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), including mTOR, PIK3CA, AKT2, and PIK3CB, involved in the M2-type polarization of macrophages, according to the genes related to M2-type polarization. We first analyzed the expression of these 13 genes in HBV-HCC and HCV-HCC, and found that mTOR was down-regulated while other genes were up-regulated (Figure S3), which was consistent with the molecular characteristics of macrophage polarization.…”
Section: Correlation Analysis Between Hub Genes and Immune Pathwaymentioning
confidence: 99%
“…Dendritic cells were increased in thyroid cancer tissue, suppressing the immune response [ 41 ]. Macrophages M2 favor the Th2 immune response, promoting tumor progression [ 42 ]. Taken together, HIF1A expression exhibited negative correlations with anti-tumor immunity and presented a positive association with tumor-suppressive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Laminins, the major biologically active component, are significantly involved in the survival and proliferation of cancer cells, malignant phenotype, angiogenesis, and development of premetastatic niches at many stages of cancer progression. Previous studies have shown the prognostic value of laminins in a range of cancers, including gastric ( 44 ), lung ( 45 ), and endometrial ( 46 ) cancer. Moreover, Galatenko et al reported that laminin expression profile analysis was more helpful for colorectal cancer prognosis than single-gene expression analysis ( 47 ).…”
Section: Discussionmentioning
confidence: 99%